Penerapan Asas Keseimbangan Pada Perjanjian Pengikatan Jual Beli Rumah Sebagai Perlindungan Hukum Pembeli Atas Wanprestasi Developer - Noormansyah, Naufal Afrian; Taupiqqurrahman, Taupiqqurrahman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 01 (2023)DO - 10.24843/AC.2023.v08.i01.p4, 2023)
The purpose of this paper is to find out the concept of applying the principle of balance in the sale and purchase binding agreement with the developer and also to examine the principle of balance to protect buyers from the developer's default. This study uses normative legal research methods with statutory approaches and legal concept approaches. The conclusion obtained from this study is PPJB which is standard in nature often creates an imbalance between buyers and developers, with the potential for developers to dominate and benefit from unequal agreements. To avoid this and ensure fair and balanced agreements, it is necessary to apply the principle of balance in preparing the PPJB. The principle of balance that is well implemented in the agreement can be seen in the actions of the parties, the contents of the agreement, and its implementation. PPJB is very important in house buying and selling transactions, especially in the pre-project selling sales system, because it functions as a preventive legal protection for the buyer in the event that the developer does not fulfill the agreement. Therefore, PPJB must be prepared with the principle of balance including including provisions that guarantee the protection of buyers from potential default developers.